Motor dysfunction as research domain across bipolar, obsessive-compulsive and neurodevelopmental disorders - Hirjak, Dusan; Meyer-Lindenberg, Andreas; Fritze, Stefan; Sambataro, Fabio; Kubera, Katharina Maria; Wolf, Robert Christian (Neuroscience & biobehavioral reviews, 2018)
Although genuine motor abnormalities (GMA) are frequently found in schizophrenia, they are also considered as an intrinsic feature of bipolar, obsessive-compulsive, and neurodevelopmental disorders with early onset such as autism, ADHD, and Tourette syndrome. Such transnosological observations strongly suggest a common neural pathophysiology. This systematic review highlights the evidence on GMA and their neuroanatomical substrates in bipolar, obsessive-compulsive, and neurodevelopmental disorders. The data lends support for a common pattern contributing to GMA expression in these diseases that seems to be related to cerebello-thalamo-cortical, fronto-parietal, and cortico-subcortical motor circuit dysfunction. The identified studies provide first evidence for a motor network dysfunction as a correlate of early neurodevelopmental deviance prior to clinical symptom expression. There are also first hints for a developmental risk factor model of these mental disorders. An in-depth analysis of motor networks and related patho-(physiological) mechanisms will not only help promoting Research Domain Criteria (RDoC) Motor System construct, but also facilitate the development of novel psychopharmacological models, as well as the identification of neurobiologically plausible target sites for non-invasive brain stimulation.
Available online 17 September 2018
Gesehen am 27.01.2020